(untitled) - FAO (Rome, 1999)
The report discussed were: reviews of recommendations from CWP 17th; agency programmes in fishery statistics; harmonization among agency databases; exchange and dissemination of information and statistics; integrated fisheries monitoring; definition of nationality of catch; major fishing area modifications; statistical implications of the Precautionary Approach; fishery trade data; socio-economic indicators for fisheries...
Keywords: fisheries